Autobiography of Sir John Rennie, F.R.S., past president of the Institution of Civil Engineers comprising the history of his professional life, together with reminiscences dating from the commencement of the century to the present time. - Rennie, John, Sir, 1794-1874 (E. & F.N. Spon, 1875)
This is an unexpurgated account of the life of an engineer in the 19th century.